A multidimensional longitudinal dataset on functional somatic syndromes - Peyman Adibi; Simindokht Kalani; Alireza Ani; Hassan Shahoon; Awat Feizi; Hamidreza Roohafza (Data in Brief, 2023)
Functional disorders represent a prevalent health issue, significantly impacting both individuals and healthcare systems. This multidisciplinary dataset aims to enhance our comprehension of the complex interplay among various factors that contribute to functional somatic syndromes. The dataset comprises data from seemingly healthy adults (aged 18-65) in Isfahan, Iran, who were randomly selected and monitored for four consecutive years. The research data encompasses seven distinct datasets: (a) functional symptom evaluations across multiple body organs, (b) psychological assessments, (c) lifestyle factors, (d) demographic and socioeconomic variables, (e) laboratory measurements, (f) clinical examinations, and (g) historical information. A total of 1930 participants were enrolled at the study's outset in 2017. The first, second, and third annual follow-up rounds were completed with 1697 (2018), 1616 (2019), and 1176 (2020) participants, respectively. This dataset is made available for further analysis by a diverse range of researchers, healthcare policymakers, and clinicians.